AN ASSESSMENT OF SOCIAL STUDIES MAJORS‟ WHOLE-BRAIN LEARNING SYSTEMS - Reynaldo B. Inocian; Gerome L. Lasala (European Scientific Journal, ESJ, 2014)
Robert Frost said, “The brain is a wonderful organ. It starts workingthe moment you get up in the morning and does not stop until you get intothe office”. It is like a jungle of rainforest wired with so manyinterconnections once it functions (Edelman, 1992). This study is anassessment of the Bachelor of Secondary Education (BSED) Social Studiesmajors‘ whole-brain learning systems from October 2013 to April 2014.Through a purposive sampling, the case study employs mixed methods ofboth quantitative and qualitative approaches. The assessment results betweenGardner‘s Multiple Intelligences and Herman‘s Brain Quadrants areconsistent, that is, a safe-keeping-self matches a connection of a doubledominantleft brain. Though social masking is prevalent on personalnarratives, self-preservation is used to camouflage harsh social realities.What is hidden inside, the group projects to be friendly in search of socialapproval, a concealed angst within their personality that purges inner voicesto be heard in response to the development of the whole-brain learningsystem. Their attitudes and values toward social studies remark a high levelof strong agreement, with average content knowledge, but these still needattention to balance instruction and fill in the limited right brain exposurethat would improve the group‘s content knowledge acquisition in socialstudies where it is found less efficient.